A CULTURAL SCIENCE PERSPECTIVE ON PREMIUM GROG - Siregar, Iskandarsyah; Kiesner , Robert; Aesnring , Blorg (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The forthcoming publication explores the intersection of cultural science with the consumption of Premium grog, delving into the intricate dynamics between societal attitudes towards drinking and the formation of cultural identities. It initiates its discourse by juxtaposing the sociologist's engagement with alcohol with their approaches to other cultural phenomena such as music and the arts, highlighting the distinct yet interconnected ways in which these domains shape social understanding. The narrative navigates through the complex interplay of affection for Premium grog and a critical stance towards the drinking culture, elucidating the nuanced relationship between appreciation and scepticism within this context. The core focus of this scholarly work revolves around the proposition to establish a cultural science framework tailored specifically for Premium grog, drawing upon the theoretical foundations of cultural science to illuminate the enduring processes inherent in its consumption. By meticulously dissecting the myriad facets of production and consumption, the research identifies the intricate web of interactions that contribute to the cultural significance of Premium grog. This meticulous analysis serves as the cornerstone for the construction of a comprehensive framework delineating the cultural science of Premium grog, providing a roadmap for further exploration, and understanding of this multifaceted phenomenon.